Autologous subcutaneous adipose tissue transplants improve adipose tissue metabolism and reduce insulin resistance and fatty liver in diet‐induced obesity rats. Issue 17 (31st August 2016) - Torres‐Villalobos, Gonzalo; Hamdan‐Pérez, Nashla; Díaz‐Villaseñor, Andrea; Tovar, Armando R.; Torre‐Villalvazo, Ivan; Ordaz‐Nava, Guillermo; Morán‐Ramos, Sofía; Noriega, Lilia G.; Martínez‐Benítez, Braulio; López‐Garibay, Alejandro; Torres‐Landa, Samuel; Ceballos‐Cantú, Juan C.; et al.
Abstract: Long‐term dietary and pharmacological treatments for obesity have been questioned, particularly in individuals with severe obesity, so a new approach may involve adipose tissue transplants, particularly autologous transplants. Thus, the aim of this study was to evaluate the metabolic effects of autologous subcutaneous adipose tissue (SAT) transplants into two specific intraabdominal cavity sites (omental and retroperitoneal) after 90 days. The study was performed using two different diet‐induced obesity (DIO) rat models: one using a high‐fat diet (HFD) and the other using a high‐carbohydrate diet (HCHD). Autologous SAT transplant reduced hypertrophic adipocytes, improved insulin sensitivity, reduced hepatic lipid content, and fasting serum‐free fatty acids (FFAs) concentrations in the two DIO models. In addition, the reductions in FFAs and glycerol were accompanied by a greater reduction in lipolysis, assessed via the phosphorylation status of HSL, in the transplanted adipose tissue localized in the omentum compared with that localized in the retroperitoneal compartment. Therefore, the improvement in hepatic lipid content after autologous SAT transplant may be partially attributed to a reduction in lipolysis in the transplanted adipose tissue in the omentum due to the direct drainage of FFAs into the liver. The HCHD resulted in elevated fasting and postprandial serum insulin levels, which were dramatically reduced by the autologous SAT transplant. In conclusion, the specific intraabdominal localization of the autologous SAT transplant improved the carbohydrate and lipid metabolism of adipose tissue in obese rats and selectively corrected the metabolic parameters that are dependent on the type of diet used to generate the DIO model. Abstract : Autologous subcutaneous adipose tissue transplanted into two specific intraabdominal cavity sites (omental and retroperitoneal adipose tissue) improved insulin sensitivity, reduced hypertrophic adipocytes, and reduced hepatic lipid content and fasting serum‐free fatty acid concentrations in obese rats induced by high‐fat or high‐carbohydrate diets. Moreover, part of the metabolic improvement was mediated by changes in the adipose tissue lipolytic metabolism. The transplant procedure, which is an innovate method, permits to integrate physically and metabolically the transplanted adipose tissue.